New drug targets for alcoholic liver disease - Xu, Mingjiang (Hepatol Int, 2014)
Alcoholic liver disease (ALD) represents a spectrum of disorders, ranging from simple steatosis to severe alcoholic hepatitis and cirrhosis. The severe form of ALD comprises multiple problems in the liver, including inflammation, hepatocellular damage, fibrosis, and impaired liver regeneration, and likely requires combinational therapies. In this review, we discuss recently identified therapeutic targets that inhibit inflammation, ameliorate hepatocyte death, and promote liver repair in ALD, with a focus on our recent studies on the immunosuppressive drug prednisolone and the hepatoprotective cytokine interleukin-22. Clinical trials examining prednisolone plus interleukin-22 therapy for severe alcoholic hepatitis are currently under consideration.